Riverbed Sediments Control the Spatiotemporal Variability of E. coli in a Highly Managed, Arid River - Fluke, James; González-Pinzón, Ricardo; Thomson, Bruce (Frontiers in Water, 2019)
High concentrations of fecal indicator bacteria (FIB) can result in exceedance of surface water quality standards, particularly in urban areas which receive stormwater runoff. Although FIB are considered to be an indicator of mammalian waste, there is increasing evidence of regrowth in sediments of warm streams. However, the role that sediment-water interactions play on the spatiotemporal distribution of FIB is not well understood, particularly on scales relevant to water quality management. We examined E. coli loads in river water and concentrations in sediments in a 60 km reach of the Rio Grande near Albuquerque, USA to determine seasonal and spatial trends of the coupling between FIB in the water column and those in sediments. Our study reach progresses from a narrow, coarse-bottom channel (0-9.4 km) with insignificant anthropogenic FIB sources to a wide, sand-braided channel with prevalent mid-channel bars and islands (25-61.5 km) that flows through a city with 1 million inhabitants. At upstream sites, we observed low E. coli loads during low discharges and low sediment E. coli concentrations. Conversely, downstream sites had high E. coli loads and high sediment concentrations year-round. Using a simple framework to quantify sediment-water interactions and E. coli transferability, we found that the fine riverbed sediments present at downstream sites served as a source of E. coli to the overlying water and that they promoted the survival of E. coli along this subreach, contributing to frequent violations of the stream standard. Therefore, we propose that sediment-water interactions should be explicitly considered in water quality management, protection, and improvement efforts.